Análise Espacial do Desenvolvimento e das Desigualdades no Território Sudoeste Baiano - Allisianne Krystina Saraiva de Figueiredo (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
This study aims to analyze the development of the Southwest Territory of Bahia (TSB) from a multidimensional perspective, identifying the disparities and similarities between the municipalities that compose it. It starts from a literature review based on theories of regional economics, more specifically on the uneven development between regions. The use of the Factor Analysis technique allowed to reduce the set of variables facilitating the analysis of the social, economic, demographic, political-institutional, environmental and cultural indicators observed in this study. From the factorial scores, the cluster analysis was performed considering the similarities between the municipalities with the dimensions analyzed. There was a great concentration of economic growth and development in the city of Vitória da Conquista, the main urban-center of the Territory. In all the analyzed dimensions, the municipalities presented a little expressive economic dynamics associated to the low performance in social indicators, resulting in an uneven and heterogeneous development. Factor analysis revealed economic growth and infrastructure as the determinants of development and inequality in TSB, and also made it possible to rank municipalities in order of better for the worse condition. The clustering analysis pointed out three distinct development groups, confirming the scenario of heterogeneity existing in the TSB, in which Vitória da Conquista performs quite differently from the other municipalities. It was observed polarization and concentration of the economic growth resulting from the little economic attractiveness of the majority of the municipalities that compose the Territory. These analyzes can support territorial management and planning policies to reduce disparities in this Territory.